HASIL DAN KOMPONEN HASIL BEBERAPA CALON VARIETAS JAGUNG HIBRIDA DI SULAWESI SELATAN - Febri hendrayana; Chitra Dewi Yulia Christie; Nia Agus Lestari (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
The Agrotechnology Study Program, Faculty of Agriculture, Kahuripan University of Kediri (UKK) conducted an adaptation test in South Sulawesi which aimed to determine the productivity and agronomic appearance of prospective hybrid corn varieties from breeding compared to varieties that already exist in Indonesian corn centers. The testing activity was carried out at IP2TP Balitsereal, Bontosalama Village, Bajeng District, Gowa Regency, South Sulawesi from August to December 2022. The genetic material used consisted of 7 hybrid corn test hybrids, namely: UKK01, UKK02, UKK03, UKK04, UKK05, UKK06, and UKK07 and 2 comparison varieties, namely NK 7328 and ADV 789. The test was arranged using a Randomized Completed Block Design, 3 replicates. The results of the adaptation test show that the test hybrid with a productivity of 8.74 t/ha – 10.03 t/ha is superior to the comparator variety with a productivity of 11.75 t/ha for NK 7328 and 11.78 t/ha for ADV 789.